Analisis Pelaksanaan Manajemen Kearsipan Dalam Pengelolaan Tata Persuratan di MAS EX PGA Univa Medan - Darmansah, Tengku; Savitri, Intan; Oktaviani, Dita; Widyana, Tasya; Maulida, Sifa (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The existence of letters and archives with the information they contain is the backbone of management and organization. Both have an important role in the process of presenting information for schools and institutions to make decisions and formulate policies, therefore, to be able to present complete, fast and correct information there must be good working systems and procedures. The aim is to find out the analysis of the implementation of archives management in managing correspondence at Mas Ex PGA Univa Medan and to find out archival obstacles in managing correspondence. This research uses qualitative research, data collection techniques through interviews, observation and documentation. Data analysis by data reduction, data presentation and drawing conclusions. The results of the research show that First, the analysis of the implementation of archives management in the management of correspondence at Mas Ex PGA Univa Medan includes several activities, namely, the implementation of archives management in the management of correspondence at Mas Ex PGA Univa Medan, the obstacles faced in the implementation of archives management at Mas Ex PGA Univa Medan, the right solution to improve the quality of archives management at Mas Ex PGA Univa Medan.